2008
DOI: 10.1038/npp.2008.42
|View full text |Cite
|
Sign up to set email alerts
|

Loudness Dependence of Auditory Evoked Potentials as Indicator of Central Serotonergic Neurotransmission: Simultaneous Electrophysiological Recordings and In Vivo Microdialysis in the Rat Primary Auditory Cortex

Abstract: Serotonin released in synapsis is one of the key neurotransmitters in psychiatry and psychopharmacology. The loudness dependence of auditory evoked potentials (LDAEP) has been proposed as a marker for central serotonergic neurotransmission. Several findings in animals and humans support this hypothesis. However, the in vivo measurement of cortical extracellular serotonin levels has never been performed simultaneously with the recording of auditory evoked potentials. The interrelationship between low cortical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…Furthermore, these findings support previous studies demonstrating a relationship between higher central serotonergic functioning and a weaker LDAEP (e.g. Juckel et al 1997;Wutzler et al 2008). The current findings were not moderated by either gender or 5-HTTLRP genotype, and plasma drug levels did not correlate with the LDAEP in the sertraline group.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Furthermore, these findings support previous studies demonstrating a relationship between higher central serotonergic functioning and a weaker LDAEP (e.g. Juckel et al 1997;Wutzler et al 2008). The current findings were not moderated by either gender or 5-HTTLRP genotype, and plasma drug levels did not correlate with the LDAEP in the sertraline group.…”
Section: Discussionsupporting
confidence: 85%
“…For example, in vivo microdialysis studies have revealed that 5-HT levels in the primary auditory cortex modulate the LDAEP in animals (Juckel et al 1997;Wutzler et al 2008). Further, an altered LDAEP has been demonstrated in psychiatric disorders (and some subtypes) where the serotonergic system is implicated, including major depressive disorder (Fitzgerald et al 2009;Park et al 2010), schizophrenia (Juckel et al 2008a;Gudlowski et al 2009;Park et al 2010) and bipolar disorder (Park et al 2010).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, Juckel et al (1999) reported differential effects of microinjection of a 5-HT 1A agonist and a 5-HT 1A antagonist into the dorsal raphe nucleus on the intensity dependence of auditory evoked potentials recorded epidurally from the primary and secondary auditory cortex in behaving cats. Futhermore, Wutzler et al, 2008 showed that the increase of serotonin levels after citalopram application in rats was significantly related to a decrease of LDAEP of the N1 component.…”
Section: Loudness-dependent Auditory Evoked Potentialmentioning
confidence: 99%